2014
DOI: 10.3389/fneur.2014.00002
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Closed-Head Model of Mild Traumatic Brain Injury Caused by Primary Overpressure Blast to the Cranium Produces Sustained Emotional Deficits in Mice

Abstract: Emotional disorders are a common outcome from mild traumatic brain injury (TBI) in humans, but their pathophysiological basis is poorly understood. We have developed a mouse model of closed-head blast injury using an air pressure wave delivered to a small area on one side of the cranium, to create mild TBI. We found that 20-psi blasts in 3-month-old C57BL/6 male mice yielded no obvious behavioral or histological evidence of brain injury, while 25–40 psi blasts produced transient anxiety in an open field arena … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
105
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 76 publications
7
105
2
Order By: Relevance
“…41,42 Thus, in the progeny of a cross between a floxed Thy1-EYFP reporter mouse and an emx1-Cre driver mouse, nearly all excitatory cortical and many amygdalar neurons express EYFP. [41][42][43] Although emx1 has not been reported to be expressed in the retina, we found that about 5% of retinal ganglion cells also express EYFP. The floxed Thy1-EYFP reporter mice (purchased from JAX) and emx1-Cre driver mice (purchased from the Mutant Mouse Regional Resource Consortium, or MMRRC) were maintained as colonies at the University of Tennessee Health Science Center (UTHSC).…”
Section: Animalscontrasting
confidence: 55%
See 2 more Smart Citations
“…41,42 Thus, in the progeny of a cross between a floxed Thy1-EYFP reporter mouse and an emx1-Cre driver mouse, nearly all excitatory cortical and many amygdalar neurons express EYFP. [41][42][43] Although emx1 has not been reported to be expressed in the retina, we found that about 5% of retinal ganglion cells also express EYFP. The floxed Thy1-EYFP reporter mice (purchased from JAX) and emx1-Cre driver mice (purchased from the Mutant Mouse Regional Resource Consortium, or MMRRC) were maintained as colonies at the University of Tennessee Health Science Center (UTHSC).…”
Section: Animalscontrasting
confidence: 55%
“…The overpressure air blast is delivered by a small horizontally mounted air cannon system, 40,43 consisting of a modified paintball gun (Invert Mini, Empire Paintball, Sewell, NJ), pressurized air tank, and x-y table secured onto a medium-density fiberboard (Fig. 1).…”
Section: Tbi Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of mTBI are currently unknown, and there is no consensus in the literature of injury mechanisms resulting in mTBI as a result of blast, which further emphasizes the need for additional research in the topic. Theories of possible injury mechanisms caused by overpressure exposure include soft-tissue damage from shearing [4][5][6][7], distortion of cellular structures and cell death in the brain [5,[8][9][10][11][12][13][14], and intracranial fluid cavitation [5,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to diagnose mTBI by conventional MRI. Additionally, CT and conventional MRI performance is not strongly correlated with the severity and prognosis of patients constantly (9)(10)(11). Thus, it is essential to find suitable method or biomarkers to detect mTBI.…”
Section: Introductionmentioning
confidence: 99%